PREPARATION OF FINANCIAL REPORTS BASED ON SAK EMKM: STUDY ON MSMEs IN ARU ISLANDS, MALUKU - Fanny Anakotta; Elna Marsye Pattinaja; Yohanes Warkula; Selva Temalagi (SEAN Institute, 2023)
MSMEs are one of the driving forces of a nation's economy because they play an important role in growth and employment in Indonesia, especially in Aru Islands Regency, Maluku-Indonesia. With the development of MSMEs in reporting financial reports, micro, small and medium financial accounting standards (SAK EMKM) were issued, which are expected to provide an overview of the performance of related MSME management. The research objective in this study was to find out whether the preparation of financial reports by MSMEs was in accordance with SAK EMKM. This research is a qualitative research using the case study method by collecting data through interviews and documentation. Based on the results of the study, it shows that MSMEs have not implemented the preparation of financial reports in accordance with SAK EMKM. MSMEs only prepare profit and loss reports which serve as a reference for MSMEs to determine profit or loss conditions, and MSMEs do not prepare balance sheets and notes to financial reports. Both of which are important for MSME to prepare. The preparation of income statements is only simple by utilizing technology as a medium for obtaining knowledge. In addition, there is no understanding from MSME owners as well as preparing financial reports which results in no understanding of how to properly and correctly prepare MSME financial reports in accordance with SAK EMKM